2003
DOI: 10.1002/pmic.200390061
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic protein expression of lean mice and obese diabetic mice treated with peroxisome proliferator‐activated receptor activators

Abstract: The peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that modulate lipid and glucose homeostasis. In the clinic, PPARalpha and PPARgamma agonists are used to treat hypertriglyceridemia and insulin resistance of diabetes, respectively. To gain further insight into the molecular mechanisms underlying the therapeutic actions of these drugs, we have by two-dimensional electrophoresis and mass spectrometry performed a comparative analysis of the hepatic protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 49 publications
4
50
0
1
Order By: Relevance
“…3). A recent proteomic analysis of the effect of obesity on hepatic protein expression showed ER60 was down-regulated in obese mice (30). Adeli et al (31) showed a direct association of ER60 with apoB in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…3). A recent proteomic analysis of the effect of obesity on hepatic protein expression showed ER60 was down-regulated in obese mice (30). Adeli et al (31) showed a direct association of ER60 with apoB in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…6c). A subset of these putative biomarkers were identified by CID sequencing and found to map to enzymes belonging to metabolic functions known to be elevated in the fasting state (35). For instance, three peptides mapped to betaine-homocysteine S-methyltransferase, an enzyme involved in homocysteine metabolism; two matched to the fatty-acid binding protein L-FABP, which is linked to the transport of lipids in liver; and two mapped to 10-formyltetrahydrofolate dehydrogenase, which mediates de novo biosynthesis of purine.…”
Section: Biomarker Identificationmentioning
confidence: 99%
“…These adaptations are reflected at the protein level (35). As a general test of reproducibility, each tissue sample was analyzed in duplicate on two separate days, for a total of four datasets per sample.…”
Section: Sample Classificationmentioning
confidence: 99%
“…Proteins induced in these mechanisms may be of great importance in advancing understanding of these processes, or even be potential therapeutic targets. To our knowledge, only a few studies addressed protein expression in NASH (9)(10)(11).…”
mentioning
confidence: 99%